Recent progress on hybrid (solid/gas) blue-green fs laser system - Aristov A.; Grudtsin Y.; Zubarev I.; Ivanov N.; Krokhin O.; Losev V.; Mamaev S.; Mesyats G. A. Gennady Andreyevich; Mikheev L.; Panchenko Yu.; Ratakhin N.; Sentis M.; et al. (2010, 2010)
В фонде НТБ ТПУ отсутствует